#TITLE_ALTERNATIVE# - FADILLAH SAFARI (NIM 13603008), DIAN
Sandwich structure from natural fiber is potential to be developed as alternative material of wood and metal. This is due to its potential properties i.e. renewable, ligwas modeled htweight, and its competitive mechanical property compared to fiberglass composite. In addition, Indonesia has an abundant amount of natural resources including natural fiber. Nevertheless, sandwich structure has problem with compressive loading. This final project is a research about behavior of natural sandwich column under compressive loading. The Sandwich column consists of core (Coconut powder/latek) and face (Hemp/Epoxy or Coir/Epoxy). The sandwich column was modeled as 2-D perfect column with simply supported and uniaxial loading in MSC.Nastran. This final project has four model, that is overall buckling model, wrinkling, model with thickness variation of core, and overall buckling model with initial delamination. From analyze result, critical load of sandwich with face Hemp/Epoxy is 206,02 N/mm for overall buckling model and 306,97 N/mm for wrinkling model. In other hand, critical load of sandwich with face Coir/Epoxy is 73.65 N/mm for overall buckling model and 149.60 N/mm for wrinkling model. The analyzed result of model with thickness variation of core is that critical load increase with core thickness increasing and occur mode change from overall buckling mode to wrinkling mode after gain certain thickness. On the sandwich column occur decrease of critical load due to delamination between face and core. At experiment, on sandwich column occur delamination and its critical load approach the result of numerical method for model with 40% initial delamination.